Hidden diversity in the Brazilian Atlantic rainforest: the discovery of Jurasaidae, a new beetle family (Coleoptera, Elateroidea) with neotenic females - Rosa, Simone Policena; Costa, Cleide; Kramp, Katja; Kundrata, Robin (Scientific reports, 2020)
Beetles are the most species-rich animal radiation and are among the historically most intensively studied insect groups. Consequently, the vast majority of their higher-level taxa had already been described about a century ago. In the 21st century, thus far, only three beetle families have been described de novo based on newly collected material. Here, we report the discovery of a completely new lineage of soft-bodied neotenic beetles from the Brazilian Atlantic rainforest, which is one of the most diverse and also most endangered biomes on the planet. We identified three species in two genera, which differ in morphology of all life stages and exhibit different degrees of neoteny in females. We provide a formal description of this lineage for which we propose the new family Jurasaidae. Molecular phylogeny recovered Jurasaidae within the basal grade in Elateroidea, sister to the well-sclerotized rare click beetles, Cerophytidae. This placement is supported by several larval characters including the modified mouthparts. The discovery of a new beetle family, which is due to the limited dispersal capability and cryptic lifestyle of its wingless females bound to long-term stable habitats, highlights the importance of the Brazilian Atlantic rainforest as a top priority area for nature conservation.
Keywords: Rainforest; Phylogeny; Sequence Analysis, DNA; Ecosystem; Female; Brazílie; zvířata; deštný prales; Coleoptera; genetická variace; sekvenční analýza DNA; Genetic Variation; ženské pohlaví; Male; fylogeneze; Brazil; brouci; Animals; mužské pohlaví; ekosystém